Awareness about Sexually Transmitted Infections and Human Immunodeficiency Virus Infection among Patients with Genital Symptoms - Gyawalee, Madhu; Paudyal, BP; Pokhrel, DB (Nepal Journal of Dermatology, Venereology & Leprology, 2017)
Introduction: Sexually transmitted infections (STIs) are a major cause of public health problem. In developing countries, human immunodeficiency virus (HIV) infection is spreading rapidly, with sexually transmitted infections acting as a cofactor for the spread of HIV. Yet adequate awareness regarding these infections is lacking. Objective: To explore the knowledge and awareness about STIs and HIV infection in patients visiting Dermatology and Venereology Clinic of Institute of Medicine, Tribhuvan University Teaching Hospital (TUTH) with genital symptoms. Material and Methods: A cross sectional descriptive study was carried out in the department of dermato-venereology, TUTH for a period of one year. Total of 130 consecutive cases were enrolled. After taking consent and assuring confidentiality they were interviewed regarding awareness of STIs and HIV/AIDS. Results: Out of 130 cases, 95% and 98.5% had heard of an STI and HIV/AIDS respectively. Only 43.8% could mention discharge from genitalia as a symptom of STI whereas 38.5% could mention none. Most (91.5%) knew about the sexual mode of transmission of both STIs and HIV. None could mention about mother to child transmission of an STI, whereas 15% knew that an infected mother can transmit HIV to her baby. About 58% were aware that condoms could protect them from acquiring an STI, 63% perceived this as best method of prevention from HIV. When only 26% knew that being faithful to one partner is the best mode of prevention from an STI, 45% mentioned avoiding contact with multiple partners could prevent them from HIV transmission. Conclusions: Awareness programme on STIs as a whole could improve knowledge and awareness on HIV and STIs and hence prevent both.